2009
DOI: 10.4238/vol8-3gmr592
|View full text |Cite
|
Sign up to set email alerts
|

Genetic distances between popcorn populations based on molecular markers and correlations with heterosis estimates made by diallel analysis of hybrids

Abstract: ABSTRACT. Diallel analysis was used to obtain information on combining ability, heterosis, estimates of genetic distances by random amplified polymorphic DNA (RAPD) and on their correlations with heterosis, for the popcorn varieties RS 20, UNB2, CMS 43, CMS 42, Zélia, UEM J1, UEM M2, Beija-Flor, and Viçosa, which were crossed to obtain all possible combinations, without reciprocals. The genitors and the 36 F 1 hybrids were evaluated in field trials in Maringá during two growing seasons in a randomized complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…This result is widely reported in the literature, for example, Arnhold et al (2009) and Broccoli and Burak (2004) confirmed that grain yield is inversely correlated (negative genetic association) with popping expansion. The Spearman correlation coefficient estimated by Munhoz et al (2009) was not significant for 96 S3 popcorn families. Broccoli and Burak (2004) mentioned that the negative association between popping expansion and yield can affect the yield gains in simultaneous selection of a breeding population.…”
Section: Resultsmentioning
confidence: 51%
“…This result is widely reported in the literature, for example, Arnhold et al (2009) and Broccoli and Burak (2004) confirmed that grain yield is inversely correlated (negative genetic association) with popping expansion. The Spearman correlation coefficient estimated by Munhoz et al (2009) was not significant for 96 S3 popcorn families. Broccoli and Burak (2004) mentioned that the negative association between popping expansion and yield can affect the yield gains in simultaneous selection of a breeding population.…”
Section: Resultsmentioning
confidence: 51%
“…Based on the investigations on different maize genotypes with different molecular markers, relatively few suppositions have been proposed to explain the low correlations genetically. However, the fact is that this problem is not completely solved and will need further investigations aimed at analysis techniques that use molecular markers and that search for genetic explanations for the existence of significant correlations between hybrid performance and GD for some plant species and the absence of correlation in others (Munhoz et al 2009). Based on the present results we report that RAPD technique is also inefficient in analyzing of genetic structures of short duration sub-tropical maize for determination of heterosis and SCA for grain yield, and therefore can not be used in predicting hybrid performance.…”
Section: Resultsmentioning
confidence: 98%
“…Popcorn breeding programs in Brazil have emerged with the use of intra and interpopulational recurrent selection to increase productivity and popping expansion (Daros et al 2004;Faria et al 2008;Freitas Júnior et al 2009;Amaral Júnior et al 2010); composite obtainment (Rangel et al 2008;Vieira et al 2009a;Scapim et al 2010); evaluation and introduction of disease resistance in commercial materials (Miranda et al 2002;Vieira et al 2009b); evaluation of the genetic diversity for agronomical traits and molecular markers (Dandolini et al 2008;Miranda et al 2008;Munhoz et al 2009;Leal et al 2010;Trindade et al 2010); use of in vitro culture (Ricci et al 2007;Fernandes et al 2008); hybrids obtainment and its evaluation (Vieira et al 2009c;Vieira et al 2009a;Silva et al 2010).…”
Section: Introductionmentioning
confidence: 99%